(untitled) (Research, Society and Development, 2026)
Dental wear is a natural process influenced by aging, hygiene, and dietary or parafunctional habits. Non-carious cervical lesions (NCCLs) are wear defects that occur in the area near the cementoenamel junction, with a multifactorial etiology. This cross-sectional observational clinical study aimed to identify the prevalence of NCCLs and associated etiological factors in 100 patients treated at the Teaching Dental Clinic (COE) of the Faculdade Evangélica De Goianésia (FACEG). The research involved a clinical diagnosis and the application of a structured questionnaire. The clinical analysis identified a total of 698 lesions, with erosion being the most prevalent type (59.74% of total lesions). Self-reported risk factors included a high prevalence of reflux/gastritis (40.2%) and frequent acid consumption (43.1%), which correlates with the predominance of erosive lesions. Furthermore, 52% of the patients reported having occlusal interferences, and 44.1% reported tooth clenching. The distribution of lesions varied with age: erosion was significantly higher in the 18 to 30 age group (79.35%), while abfraction was more prevalent in the group over 60 years old (24.32%). It was concluded that NCCLs have a high prevalence in the studied population, with a clear predominance of erosive etiology. It is essential that the dentist performs a complete anamnesis for the management of chemical, mechanical, and functional factors, aiming for the prevention and early diagnosis of these lesions.